EFEK KOMPOSISI BEBERAPA MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Yusmaidar Sepriani; Yudi Triyanto (JURNAL AGROPLASMA, 2020)
This study aims to determine the composition effect of several growing media on the growth and production of cayenne pepper (Capsicum frutescens L). This research was carried out on the Labuhanbatu STIPER trial field, Jln. Manunggal AMD, Bakaran Batu Village, Rantau Selatan District, Labuhanbatu Regency, North Sumatra Province which began from December 2018 to March 2019. The experimental design used was Non Factorial Randomized Block Design (RBD) and each treatment was repeated 3 (three) times. Treatment consists of: P0 = Land (control), P1 = Solid + Land (1: 3), P2 = Cow Manure + Soil (1: 3), P3 = Sand + Soil (1: 3), P4 = Land + Solid + Cow Manure (2: 1: 1), P5 = Land + Solid + Sand (2: 1: 1), P6 = Soil + Cow Manure + Sand (2: 1: 1), P7 = Land + Solid + Cow + Sand Manure (1: 1: 1: 1). The results showed that the composition of solid + soil planting media with a ratio of 1: 3 (P1) can increase plant height, number of leaves and stem diameter of cayenne pepper plants. In the composition of soil + solid planting media + cow manure with a ratio of 2: 1: 1 (P4) can increase the weight of fruit crops and the number of fruit crops in cayenne pepper plants.Keywords: composition of planting media, cayenne pepper (Capsicum frutescens L).